2015
DOI: 10.5001/omj.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

The Valuable Role of Measuring Serum Lipid Profile in Cancer Progression

Abstract: Our study suggested a benefit of measuring serum levels of lipids for predicting cancer progression. Increased LDL levels can be considered a predictive factor for increasing the risk of metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…64 It has been found that there is an association between cholesterol and high HDL levels and increased risk of breast cancer. 62,63 In another study, low HDL was correlated with increased postmenopausal breast cancer risk. 65 Thereby, the association between serum HDL level and risk of breast cancer seems to be potentially influenced by menopausal status.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…64 It has been found that there is an association between cholesterol and high HDL levels and increased risk of breast cancer. 62,63 In another study, low HDL was correlated with increased postmenopausal breast cancer risk. 65 Thereby, the association between serum HDL level and risk of breast cancer seems to be potentially influenced by menopausal status.…”
Section: Introductionmentioning
confidence: 95%
“…62 Assessment of serum lipids among breast cancer, by Ghahremanfard et al, revealed highest levels of cholesterol and lipoproteins. 63 Thereby, it has been concluded that increased serum lipid levels could have an important role in the progression of cancers in women, including breast and ovarian cancers, while lower level of lipids and lipoproteins may be used as markers for discriminating gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical platforms based on Chromatography coupled with Mass Spectrometry (MS) are frequently used in Lipidomics to provide the sensitive and reproducible detection of hundreds metabolites in a single biofluid or tissue sample. Biofluids, such as blood serum and plasma are the most frequent materials utilized for clinical diagnosis, to measure the level of lipids used for prediction of cancer progression (Jelonek et al, 2013;Ghahremanfard et al, 2015;Chawda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis is another interesting area in which the lipid level can correlate with disease burden. In one study, 205 Iranian patients from Semnan Oncology Clinic were studied and there was a significant association between higher levels of serum LDL and metastasis [7]. Aggressiveness of the tumor including metastasis can be highlighted by the levels of lipids.…”
mentioning
confidence: 99%